Long-term effects of GH therapy in adult patients with Prader-Willi syndrome: a longitudinal study - Grugni, Graziano; Sartorio, Alessandro; Soranna, Davide; Zambon, Antonella; Grugni, Lucia; Zampino, Giuseppe; Crinò, Antonino (Frontiers in Endocrinology, 2023)
Prader-Willi syndrome (PWS) is a complex disorder resulting from the failure of expression of paternal alleles in the PWS region of chromosome 15. The PWS phenotype resembles that observed in the classic non-PWS GH deficiency (GHD), including short stature, excessive fat mass, and reduced muscle mass. Emerging information seems to demonstrate the maintenance of beneficial effects of GH therapy in adults with PWS. However, a small number of studies on the long-term effects of GH treatment in these individuals are available so far. In this longitudinal study, 12 obese subjects with PWS (GHD/non-GHD 6/6) were treated for a median of 17 years, with a median GH dose of 0.35 mg/day. The median age was 27.1 years. Anthropometric, body composition, hormonal, biochemical, and blood pressure variables were analyzed in all patients. Weight and Body Mass Index showed a trend toward a decrease without statistical significance (p-value= 0.0771 and p-value=0.0771, respectively), while waist circumference was significantly lower at the end of the treatment period (p-value=0.0449). Compared to the baseline, a highly significant reduction of Fat Mass % (FM%) was observed (p-value=0.0005). Lean body mass showed a not significant tendency to be increased (p-value= 0.0557). IGF-I SDS values significantly increased during GH therapy (p-value=0.0005). A slight impairment of glucose homeostasis was observed after GH therapy, with an increase in the median fasting glucose levels, while insulin, HOMA-IR, and HbA1c values remained unchanged. Considering GH secretory status, both subjects with and without GHD showed a significant increase in IGF-I SDS and a reduction of FM% after GH therapy (p-value= 0.0313 for all). Our results indicate that long-term GH treatment has beneficial effects on body composition and body fat distribution in obese adults with PWS. However, the increase in glucose values during GH therapy should be considered, and continuous surveillance of glucose metabolism is mandatory during long-term GH therapy, especially in obese patients.